2010
DOI: 10.1097/pas.0b013e3181f5539c
|View full text |Cite
|
Sign up to set email alerts
|

Invasive Ductal Carcinomas of the Breast Showing Partial Reversed Cell Polarity are Associated With Lymphatic Tumor Spread and may Represent Part of a Spectrum of Invasive Micropapillary Carcinoma

Abstract: Invasive micropapillary carcinomas (IMPC) of the breast are aggressive tumors frequently associated with lymphatic invasion and nodal metastasis even when micropapillary (MP) differentiation is very focal within the tumors. We have noticed that some breast carcinomas showing lymphatic spread but lacking histologic features of IMPC have occasional tumor cell clusters reminiscent of those of IMPC without the characteristic prominent retraction artifact. To study the clinicopathologic significance of such feature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 31 publications
3
34
0
1
Order By: Relevance
“…Cell membranes at the periphery of tumorous cell clusters were characteristically positive for EMA, indicating an inside-out pattern of reactivity. This distinctive finding is critical for identifying the MPC as confirmed previously [13,14]. MPC showed immunohistochemical findings similar to the immunohistological findings of the same tumor type without MPC.…”
Section: Discussionsupporting
confidence: 49%
“…Cell membranes at the periphery of tumorous cell clusters were characteristically positive for EMA, indicating an inside-out pattern of reactivity. This distinctive finding is critical for identifying the MPC as confirmed previously [13,14]. MPC showed immunohistochemical findings similar to the immunohistological findings of the same tumor type without MPC.…”
Section: Discussionsupporting
confidence: 49%
“…Ide et al 23 revealed 8.4% of invasive breast cancer contained the IMPC component in their cohort of 486 patients, and noted that the presence of the IMPC component alone was a significant predictive factor for LNM, even if it was detected in only a small proportion of the tumor. The study results from Acs et al 24 suggested that breast carcinomas with partial reservation of the cell polarity may have the same implications as micropapillary differentiation, and these tumors may represent parts of a spectrum of IMPCs. Complete or partial reversal of cell polarity may have a significant role in lymphatic tumor spread.…”
Section: Microscopic Pathologymentioning
confidence: 84%
“…7 The status of the HER2/neu protein expression or gene amplification in IMPC is not consistent in literature. Some studies showed HER2/ neu þ rates between approximately 10% and 30%, [14][15][16]23,24 whereas others reported between approximately 50% and 80%. 34,38,41,44 Regarding the molecular classification, more cases of IMPC fall into the luminal A and luminal B subtypes than they do with IDC-NOS.…”
Section: Immunophenotypementioning
confidence: 99%
See 1 more Smart Citation
“…The incidence of IMPC ranges from 3 to 6% [4] of all primary breast cancers. Compared to invasive ductal breast carcinoma (IDC), IMPC is characterized by cells arranged in pseudopapillary structures and surrounded by clear empty spaces lined by delicate strands of fibrocollagenous stroma [5], [6] [shown in Figure 1]. …”
Section: Introductionmentioning
confidence: 99%